Let's begin by listing out the information given to us:
2x³ + x² - 7x- 2 = 0
We will proceed to factorise, we have:
(x + 2)(2x² − 3x - 1) = 0
We will proceed to equate the factors to zero, we have:
x + 2 = 0⇒ x = -2
⇒ x = -2
2x² − 3x - 1 = 0
We will use the quadratic formula, we have:
![\begin{gathered} 2x^(2)-3x-1=0 \\ x=(-b\pm√(b^2-4ac))/(2a) \\ a=2,b=-3,c=-1 \\ x=\frac{-(-3)\pm\sqrt[]{(-3)^2-4(2)(-1)}}{2(2)} \\ x=\frac{3\pm\sqrt[]{9+8}}{4}=\frac{3\pm\sqrt[]{17}}{4} \\ x=\frac{3\pm\sqrt[]{17}}{4}\Rightarrow x=\frac{3+\sqrt[]{17}}{4},\frac{3-\sqrt[]{17}}{4} \\ x=\frac{3+\sqrt[]{17}}{4},\frac{3-\sqrt[]{17}}{4} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/w7857fhhq4omqyzss4hemk55wqfmjcyuiv.png)